Allelopathic effects of invasive weed species Abutilon theophrasti Medik., Ambrosia artemisiifolia L., Datura stramonium L. and Xanthium strumarium L. on tomato - Radivojević, Ljiljana; Sarić-Krsmanović, Marija; Gajić Umiljendić, Jelena; Šantrić, Ljiljana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Abutilon theophrasti Medik, Ambrosia artemisiifolia L., Datura stramonium L. and Xanthium strumarium L. are four well-known invasive weed species that are widespread in many crops. Laboratory experiments were conducted to evaluate the allelopathic effects of decomposition products of these four invasive weeds on seed germination and early seedling growth of tomato. The results of the study showed that decomposition products obtained from A. theophrasti, A. artemisiifolia, D. stramonium and X. strumarium had different allelopathic impacts on germination and seedling growth of tomato. The degree of inhibition or stimulation depended on weed species and type of decomposition product. Root decomposition products of all species except X. strumarium decreased the early growth of tomato (2-37%). X. strumarium had only stimulating effect on early growth of tomato (1-86%). Also, the results showed that leaves of the other three invasive weed species had stimulating effects on early growth of tomato (1-53%). Hence, the allelopathic potential of X. strumarium, as well as the leaf decomposition products of the other three invasive weed species could be used to develop an appropriate technology to improve tomato production.